Faktor Yang Berhubungan Dengan Partisipasi Anggota Kelompok Wanita Tani (KWT) Dalam Pemanfaatan Lahan Perkarangan Di Wilayah Kerja Balai Penyuluhan Pertanian (BPP) Selebar - Huriyah, Hiwayati; Fariadi, Herri; Nurmalia, Ana (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The success of yard land utilization activities intervened by government programs is inseparable from the participation of members of the Women Farmers Group (KWT). This study aims to analyze the level of participation of members of the Women Farmers Group (KWT) in the Working Area of the Selebar Agricultural Extension Center (BPP) in the utilization of yard land and to analyze what factors are associated with the participation of members of the Women Farmers Group (KWT) in the Working Area of Selebar Agricultural Extension Center (BPP) in the utilization of yard land. The research was conducted from July to August 2024. The population in this study was 116 people with a sample size of 90 people determined by proportional stratified random sampling method. Data were analyzed by Pearson product moment statistical test. The results showed that the level of participation of KWT members in utilizing the yard was in the high category. Factors that are significantly related to the level of participation of KWT members are formal education, motivation, time devotion, accuracy of counseling methods, suitability of materials, competence of extension workers, group goals, group cohesiveness and group atmosphere. While age is not significantly related.